Effect of pasteurization and ohmic heating on the detection of deoxynivalenol in craft beer wort base - Velarde Salas, Bryan Augusto (2024)
In the food and beverage industry, the presence of mycotoxins in cereals has driven the development of procedures to ensure the safety and quality of the final product. However, at the national level, this aspect has not yet been addressed in microbreweries. This research focused on determining the presence and concentration of deoxynivalenol (DON) in malt used for craft beer production, as well as the effect of pasteurization and ohmic heating on this mycotoxin. The study was conducted in two stages. In the first stage, the presence of DON in the malt was analyzed using the ELISA analytical technique with a detection level of 0,25ppm/5,0. Subsequently, in the second stage, wort was prepared using this malt, and the effects of pasteurization, as a traditional method, and ohmic heating, as an alternative method, on the mycotoxin were evaluated. For this purpose, an experimental ohmic heating equipment was developed, in which time and voltage parameters were established. The results showed a slight reduction in one of the wort batches when ohmic heating was applied to the mycotoxin, with a concentration of 0.057 µL, compared to pasteurization, where the concentration remained the same at 0.058 µL. These findings suggest that pasteurization maintains stable mycotoxin concentration levels; however, the combination with ohmic heating may be effective in mitigating the presence of mycotoxins in the wort base of craft beer, thereby contributing to its safety.